A Comparison Study on Uzbek and Turkish Idioms - Aghamuhammad Muradi (Universitas Muhammadiyah Sidoarjo, 2022)
Idioms are stereotypes spoken by the public, whose author and speaker are unknown. Idioms are available in all languages of the world. People have used idioms to express their thoughts and ideas to others effectively and in detail through short sentences. Humans have short, but also metaphoric words and sentences for purposes rather than long and meaningless sentences. The subject of this study is on idioms in Turkish and Uzbek. The idioms in these two languages encounter each other and are explained. From this comparison and explanation, it is proved that these two cultures, these two nations, these two languages and these two literatures are close to each other and of the same lineage. It is possible that some people may not know that these two nations come from the same lineage and the same geography.